THE RELATIONSHIP OF JOB SATISFACTION,TRANSFORMATIONAL LEADERSHIP, AND WORK DISCIPLINE ON PERFORMANCE EMPLOYEE WITH ORGANIZATIONAL COMMITMENT AS INTERVENING VARIABLE OF ADMINISTRATION STAFFS AT STATE MALIKUSSALEH UNIVERSITY - A Hadi Arifin; Sullaida Sullaida; Nurmala Nurmala (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2018)
Administrative staff is a decisive asset of human resources at state malikussaleh university , to improve employee performance. Employee performance change has relationship with some research variables. Analyzing the interaction of research variables to explain the relationship of Transformational Leadership, Job Satisfaction and Work Discipline above Employee Performance with organizational commitment as intervening variable. The sample in this research is the administrative staff of University Malikussaleh which amounted to 155 respondents, which was taken using sampling method, become the research respondent. Data collected using quesioner method. The data analysis technique used is path analysis with Structural Equation Modeling (SEM) method which is operated through Amos 21 program. The result of the research explains that transformational leadership, job satisfaction and work discipline have significant relation above organizational commitment and employee performance. Organizational commitment mediates the partial mediation relationship between transformational Leadership, Job Satisfaction Work Discipline and Employee Performance. Keywords: Transformational Leadership, Job Satisfaction, Work Discipline, Organizational Commitment, Employee Performance, State Malikussaleh University.